2008
DOI: 10.1016/j.ceca.2007.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-proteomic approach to excitation–contraction coupling in skeletal and cardiac muscle: Molecular insights revealed by the mitsugumins

Abstract: A comprehensive understanding of excitation-contraction (E-C) coupling in skeletal and cardiac muscle requires that all the major components of the Ca 2+ release machinery be resolved. We utilized a unique immuno-proteomic approach to generate a monoclonal antibody library that targets proteins localized to the skeletal muscle triad junction, which provides a structural context to allow efficient E-C coupling. Screening of this library has identified several mitsugumins (MG); proteins that can be localized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 70 publications
2
51
0
Order By: Relevance
“…Recent studies have also indicated a role for TRIM proteins in defense against events involving membrane penetration, such as protection against infection by various viruses, including human immunodeficiency virus (13-15). Although most of the studies concentrate on the cytosolic action of TRIM, limited reports have investigated the role of TRIM proteins in membrane signaling or recycling.We have previously established an immunoproteomics approach that allows definition of novel components involved in myogenesis, Ca 2ϩ signaling, and maintenance of membrane integrity in striated muscle (16). Using this approach, we have shown that junctophilin is a structural protein that establishes functional communication between sarcoplasmic reticulum and transverse tubule membranes at triad and dyad junctions in striated muscle (17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also indicated a role for TRIM proteins in defense against events involving membrane penetration, such as protection against infection by various viruses, including human immunodeficiency virus (13-15). Although most of the studies concentrate on the cytosolic action of TRIM, limited reports have investigated the role of TRIM proteins in membrane signaling or recycling.We have previously established an immunoproteomics approach that allows definition of novel components involved in myogenesis, Ca 2ϩ signaling, and maintenance of membrane integrity in striated muscle (16). Using this approach, we have shown that junctophilin is a structural protein that establishes functional communication between sarcoplasmic reticulum and transverse tubule membranes at triad and dyad junctions in striated muscle (17)(18)(19).…”
mentioning
confidence: 99%
“…We have previously established an immunoproteomics approach that allows definition of novel components involved in myogenesis, Ca 2ϩ signaling, and maintenance of membrane integrity in striated muscle (16). Using this approach, we have shown that junctophilin is a structural protein that establishes functional communication between sarcoplasmic reticulum and transverse tubule membranes at triad and dyad junctions in striated muscle (17)(18)(19).…”
mentioning
confidence: 99%
“…12 Thought screening of our unique immunoproteomic monoclonal antibody targeting membrane-associated proteins found in striated muscle, 15 we identified a monoclonal antibody (mAb 5259) that would recognize the subsarcolemmal space and the gap within the triad junction. Immunoaffinity purification with this antibody produced a protein of 53 kDa that we named MG53.…”
mentioning
confidence: 99%
“…Aside the RyR1, the junctional sarcoplasmic reticulum is enriched in several other proteins including the structural proteins triadin and junctin, as well as minor constituents such as JP-45, junctate and humbug, mitsugumin-29, SRP-27/TRIC-A and junctophilin-1 [4,[27][28][29]. These minor constituents play a role in the fine regulation of Ca 2+ release from the SR or are involved in maintaining the structural integrity of the Ca 2+ release machinery.…”
Section: Excitation-contraction Couplingmentioning
confidence: 99%